Pembelajaran Diferensiasi Dalam Pendidikan Agama Kristen Untuk Meningkatkan Pemahaman Peserta Didik Tentang Firman Tuhan - Zebua, Frendi Sofyan; Gulo, Elniat Hati Putri; Gulo, Suriani; Zebua, Augustina; Gulo, Sastra Marneta Rius (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2024)
This study aims to analyze the application of differentiated learning models in the context of Christian Education, specifically in enhancing students' understanding of the Word of God. The background of this research is based on the challenges in accommodating diverse student learning styles and the need to create more inclusive and effective teaching methods. This research employs a literature review approach, examining various sources of literature related to differentiated learning and its application in religious education. Data were collected through document studies, articles, journals, and books relevant to the topic. The data analysis technique used is thematic analysis to identify patterns and key themes emerging from the literature. The results of the study show that differentiated learning can enhance students' understanding of the Word of God, the development of Christian character, as well as students' motivation and engagement. However, challenges arise, including the increased workload for teachers, potential dependence on specific learning styles, and difficulties in measuring students' deep understanding. Therefore, a more balanced approach is needed, along with further research to address these challenges.